Sensory Monitor Arm - ERGOARM Sdn Bhd / Muhammad Izzat Isa - Isa, Muhammad Izzat (2020)
A monitor arm is a somewhat robotic looking arm that attaches to the desk, wall, or ceiling and raises the monitor to the personal ideal height. It adjusts easily according to own working style — whether stand, sit, or do a mix of both throughout the day. The benefit of a monitor arm is that it allows the user to move their computer monitor screen and thereby vary the position of the screen relative to their eyes, keyboard (hands) and the rest of the body. Thus, ErgoArm Sdn bhd has developed a new product that will bring change to the monitor arm technology. The new monitor arm by ErgoArm Sdn Bhd is equipped with presence sensor that will detect the movement of the user. The arm will move accordingly towards user’s position so that the user will not have to move the arm manually. A target market refers to a group of potential customers to whom a company wants to sell its products and services. This group also includes specific customers to whom a company directs its marketing efforts. A target market is one part of the total market for a good or service. Consumers who make up a target market share similar characteristics including buying geography, buying power, demographics, and incomes. Thus, ErgoArm Sdn bhd has planned our own targeted group of customers. The targeted groups are the ones that are working and those age between 18 and 55 years’ old. With a careful and thorough research, ErgoArm Sdn Bhd is in the line of success to make a breakthrough in the market.